2018
DOI: 10.5817/cp2018-2-3
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week randomized controlled pilot study of dance exergaming in a group: Influence on psychosocial factors in adolescent girls

Abstract: Dance exergaming, which involves playing an interactive video game that requires the player to make upper and lower body movements by dancing to music, may provide a social physical activity experience that positively impacts psychosocial health. The objective of this randomized controlled study was to examine the effects of group-based dance exergaming on adolescent girls’ psychosocial health including enjoyment, subjective health, perceived peer support, and health-related quality of life. Forty-one adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Additionally, dance training helps to develop social skills because dance comes with a set of social etiquette rules and protocols that make this activity a type of multilevel social hobby ( Novack, 1990 ; DeMers, 2013 ). Studies show that dance training encourages the development of group awareness, self-discipline, impulse-control and, respect for others ( Lobo and Winsler, 2006 ; Staiano et al, 2018 ). For example, a study showed that a creative dance program could enhance the level of social competence among pre-schoolers, while also reducing their behavior problems ( Lobo and Winsler, 2006 ).…”
Section: A Wheel Of Dancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, dance training helps to develop social skills because dance comes with a set of social etiquette rules and protocols that make this activity a type of multilevel social hobby ( Novack, 1990 ; DeMers, 2013 ). Studies show that dance training encourages the development of group awareness, self-discipline, impulse-control and, respect for others ( Lobo and Winsler, 2006 ; Staiano et al, 2018 ). For example, a study showed that a creative dance program could enhance the level of social competence among pre-schoolers, while also reducing their behavior problems ( Lobo and Winsler, 2006 ).…”
Section: A Wheel Of Dancementioning
confidence: 99%
“…For example, a study showed that a creative dance program could enhance the level of social competence among pre-schoolers, while also reducing their behavior problems ( Lobo and Winsler, 2006 ). In another study, Staiano et al (2018) showed that the experience of dance exergaming is linked to subjective health, stabilized peer conflicts, and pleasurable physical activity in adolescent girls ( Staiano et al, 2018 ).…”
Section: A Wheel Of Dancementioning
confidence: 99%
“…Although some researchers (Choi et al, 2016;Esakia et al, 2017;Zhao et al, 2017) are investigating the potential of wearable devices for encouraging participation in physical activity and positive group cohesion, there is not enough research examining the effects of social interaction and social connectedness in larger groups. Additionally, although some researchers are beginning to study the effects of group play and have found that group exergaming can provide enjoyable physical activity experiences (Staiano et al, 2018), there is very little research on how to form groups that motivates continued play.…”
Section: Social Experiencesmentioning
confidence: 99%
“…: (Choi, Oh, Edge, Kim, & Lee, 2016;Esakia et al, 2017;Zhao et al, 2017)) are investigating the potential of wearable devices for encouraging participation in physical activity and positive group cohesion, there is not enough research examining the effects of social interaction and social connectedness in larger groups. Additionally, although some researchers are beginning to study the effects of group play and have found that group exergaming can provide enjoyable physical activity experiences (Staiano, Beyl, Hsia, Katzmarzyk, & Newton, 2018), there is very little research on how to form groups that motivates continued play.…”
Section: Social Experiencesmentioning
confidence: 99%